EFFECT OF NANO AND CHEMICAL FERTILIZATION WITH NPK AND CHELATED ZINC ON VEGETATIVE GROWTH OF TAIFI AND KAMALI GRAPE CULTIVARS - Yousra M. Saleh Aljubori; Nabil M. Ameen Alimam; Shawkat M. Al-Atrushy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This research was performed during the 2021 seasons in private orchard located in Bara-Bhar-Duhok governorate to study the effect of soil application of chemical and Nano-NPK, foliar spray with chelated Nano-Zinc and their interaction on vegetative growth of Taifi and Kamali grape cultivars (Vitis vinifera L.). NPK (20:20:20) was added to the soil at five levels (0, 216 g.vine-1, 324 g.vine-1 chemical NPK, 3.24 and 6.48 g.vine-1 Nano-NP (, chelated Nano-Zinc was added at three concentration (0, 100 and 200 mg.l-1). The results showed the superiority of the Taifi cultivar in traits of number of leaves per vine, Single leaf Area and leaves dry weight over the Kamali cultivar, while Kamali cultivar was superiority in traits of leaf area per cluster ratio and total chlorophyll over the Taifi cultivar. Soil application of chemical and Nano-NPK and foliar application of Nano-zinc fertilizer achieved significant increase in vegetative growth (number of leaves, Single leaf Area, and total leaves area per vine, total chlorophyll and leaves dry weight) compare to control.  Furthermore, combination among high concentration of Nano-NPK, Nano-zinc for Taifi and Kamali cultivars improved all parameters in comparison with the control.